Molecular and Neurochemical Evaluation of the Effects of Etizolam on GABAA Receptors under Normal and Stress Conditions - Sanna, Enrico; Pau, Davide; Tuveri, Francesca; Massa, Federico; Maciocco, Elisabetta; Acquas, Cinzia; Floris, Chiara; Fontana, Simona N.; Maira, Giovanna; Biggio, Giovanni (Arzneimittelforschung, 1999)
The thienobenzodiazepine derivative etizolam (CAS 40054-69-1, 6-(o-chlorophenyl)-8-ethyl-1-methyl-4H-s-triazolo-(3,4-c)thienol (1,4)diazepine) is a potent anxiolytic with a pharmacological profile similar to that of classical benzodiazepines. In order to rationalize the therapeutic use of etizolam, its pharmacodynamics properties on GABAA receptors were investigated by a comparative study with other ligands on human recombinant GABAA as well as rat brain native receptors. Etizolam inhibited in a concentration-dependent manner [3H]flunitrazepam (CAS 1622-62-4) binding to rat cortical membranes, with an affinity of 4.5 nmol/l greater than that of alprazolam (CAS 28981-97-7) (7.9 nmol/l). Ethizolam enhanced GABA-induced Clcurrents in oocytes expressing human cloned GABAA receptors. With α1β2γ2S subunit combination, etizolam produced a 73% increase in GABA-induced currents with an EC50 of 92 nmol/l. At the same receptor type, alprazolam showed a higher degree of potentiation and potency (98%, EC50 56 nmol/l). At α2β2γ2S or α3β2γ2S subunit constructs, the effects of etizolam were similar to those of alprazolam. Flumazenil (CAS 78755-81-4) completely blocked both etizolam and alprazolam effects on GABA-induced currents. Etizolam, administered i.p., was uneffective in changing ex vivo t-[35S]butylbicyclophosphorothionate ([35S]-TBPS) binding to rat cerebral cortex, whereas alprazolam and abecarnil (CAS 111841-85-1) significantly reduced this parameter. However, etizolam similarly to abecarnil and alprazolam, antagonized isoniazid-induced increase (61%) in [35S]-TBPS binding to rat cortical membranes. Further, etizolam inhibited in a dose-dependent manner basal acetylcholine release from both hippocampus and prefrontal cortex, and reversed foot-shock-induced increase of basal acetylcholine release to a control level. Altogether, these results suggest that etizolam may have a reduced intrinsic activity, at least at specific subpopulations of GABAA receptors. This property, together with the pharmacokinetic indication of a short-acting drug, may characterize etizolam as a ligand endowed with less side-effects typical of full agonits such as diazepam (CAS 439-14-5) and alprazolam. Finally, given its marked efficacy under conditions of GABAergic deficit, etizolam may represent a possible drug of choice with reduced liability to produce tolerance and dependence after long-term treatment of anxiety and stress syndromes.
Keywords: Anxiolytics; Benzodiazepines; CAS 40054-69-1; Etizolam; GABAA receptors, partial agonists; Stress